Hypermobility syndrome: an internist's view - N A Shostak; Natalia Grigoryevna Pravdyuk; L A Kotlyarova (Современная ревматология, 2012)
The paper provides a clinical assessment and approaches to therapy for hypermobility syndrome, one of the undifferentiated forms of connective tissue dysplasia.